ASSISTANCE IN ENTREPRENEURSHIP DEVELOPMENT TUTORING "LESSON-JA" IN SUKAGALIH VILLAGE, MEGAMENDUNG DISTRICT, BOGOR REGENCY, WEST JAVA - Muna, Siti Umamah Naili; Tarigan, Asmara Iriani; Herlinawati, Elin; Idayani, Darsih; Hidayat, Wahyu; Septiani, Pani (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
The purpose of this service is to provide assistance in entrepreneurial development to students as LESSON-JA tutoring owners. LESSON-JA tutoring have the potential to be developed so that they can become more well-managed tutoring considering that this tutoring is needed by local residents and residents in other villages in learning assistance for students to learn from home. The method used is Participatory Learning through participatory in partners with discussion, practice and demonstration materials. Results Partner assistance has succeeded in determining good management strategies related to tutoring curriculum, calistung learning materials, good management strategies related to human resources and marketing, and completing LESSON-JA tutoring facilities and infrastructure. In addition, online mentoring is carried out to discuss the initial tasks that have been done by partners. The discussion of LESSON-JA tutoring assignments includes how to arrange a lesson schedule on the template provided, fill in student progress cards, and use Google Drive. Other additions such as assignment files are merged in the LESSON-JA tutoring management document. With the availability of LESSON-JA tutoring management documents and LESSON-JA lessons that have been equipped with learning media (books and teaching aids) and classroom facilities, partners have shown progress from mentoring and achieving entrepreneurial change outcomes in a more managed direction, namely from tutoring to tutoring. Other additions such as task files are merged in the LESSON-JA management document. With the availability of LESSON-JA tutoring management documents and LESSON-JA tutoring that have been equipped with learning media (books and teaching aids) and classroom facilities, partners have shown progress from mentoring and achieving entrepreneurial change outcomes in a more managed direction, namely from tutoring to tutoring.